Bad film histories : ethnography and the early archive - Groo, Katherine (University of Minnesota Press, 2019)
A vital work that unsettles the authority of the archive, the author daringly takes readers to the margins of the film record, addressing the undertheorization of film history and offering a rigorous corrective. Taking ethnographic cinema as a crucial case study, the author challenges standard ways of thinking and writing about film history and questions widespread assumptions about what film artifacts are an what makes them meaningful. Rather than filling holes, the author endeavors to understand the imprecisions and absences that define film history and its archives, boldly reexamining what early ethnographic cinema is.